1996
DOI: 10.1128/mcb.16.5.2295
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Posttranscriptional Regulation of C/EBPα and C/EBPβ Isoform Expression during the Lipopolysaccharide-Mediated Acute-Phase Response†

Abstract: The mRNAs of the CCAAT/enhancer-binding trans-activator proteins (C/EBP␣ and C/EBP␤) serve as templates for the differential translation of several isoforms which have specific transcriptional regulatory functions. By using an oligonucleotide corresponding to the C/EBP binding site of the mouse ␣ 1 -acid glycoprotein promoter, we detected multiple forms of C/EBP␣ and C/EBP␤ proteins in the mouse liver that have DNA-binding activity. By using specific antisera, we detected C/EBP␣s with molecular masses of 42, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
160
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 58 publications
13
160
2
Order By: Relevance
“…Our studies identified oxidatively modified mouse heart mitochondrial ETC proteins whose levels of modification in some cases correlated with the decrease in complex activity as is predicted by the Free Radical Theory of Aging [9,16,17,27,33] whereas in others, modifications had no effect on functions, thus suggesting the interaction of other factors. The decrease in CI and CV enzyme functions is consistent with our hypothesis that mitochondrial dysfunction in the aging heart may be due to the accumulation of oxidatively modified proteins.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Our studies identified oxidatively modified mouse heart mitochondrial ETC proteins whose levels of modification in some cases correlated with the decrease in complex activity as is predicted by the Free Radical Theory of Aging [9,16,17,27,33] whereas in others, modifications had no effect on functions, thus suggesting the interaction of other factors. The decrease in CI and CV enzyme functions is consistent with our hypothesis that mitochondrial dysfunction in the aging heart may be due to the accumulation of oxidatively modified proteins.…”
Section: Discussionsupporting
confidence: 51%
“…Alternatively, failure to replace the dissociated α-chain may account for the decreased ATP production, which is a hallmark of increasing mitochondrial dysfunction with aging. Previously, it has been shown that MDA modified β-chain is associated with decreased heart CV function with age [33]. Since, we did not find MDA-modified β-chain in BN-PAGE separated CV suggests that it may have dissociated from the intact complex.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations